2012
DOI: 10.1111/j.1755-0238.2012.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Subregional survey of aroma compounds in Marlborough Sauvignon Blanc wines

Abstract: Background and Aims Marlborough is the largest wine‐growing region in New Zealand and Sauvignon Blanc varieties represent over 60% of the vineyard area. The main compounds responsible for the most intense aromas in Sauvignon Blanc wines have been assumed to be methoxypyrazines and varietal thiols; however, the aromatic potential of Sauvignon Blanc wines should not be limited to these compounds. Methods and Results Commercially pressed juices from seven Marlborough subregions were fermented using replicated res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 46 publications
4
24
1
Order By: Relevance
“…Esters, fatty acids and higher alcohols have a fermentative origin, while terpenes and certain volatile thiols are classed as varietal aromas (Tominaga & Dubourdieu, 2003;Swiegers at al., 2005;Polásková et al, 2008). Concentrations found in the wines made in this study are in accordance with previously reported research (Francis & Newton, 2005;Benkwitz et al, 2012;Jouanneau et al, 2012). Moreover, differences were found for the aroma composition between the different wine treatments ( Table 2).…”
Section: Gsh Concentrations During Alcoholic Fermentationsupporting
confidence: 92%
“…Esters, fatty acids and higher alcohols have a fermentative origin, while terpenes and certain volatile thiols are classed as varietal aromas (Tominaga & Dubourdieu, 2003;Swiegers at al., 2005;Polásková et al, 2008). Concentrations found in the wines made in this study are in accordance with previously reported research (Francis & Newton, 2005;Benkwitz et al, 2012;Jouanneau et al, 2012). Moreover, differences were found for the aroma composition between the different wine treatments ( Table 2).…”
Section: Gsh Concentrations During Alcoholic Fermentationsupporting
confidence: 92%
“…The volatiles were extracted by headspace-solid phase microextraction (HS-SPME) and separated by GC-MS. The method was modified from Jouanneau, et al [26]. The standards were grouped into three mixtures according to chemical classes and retention time, in order to optimize the separation.…”
Section: Methodsmentioning
confidence: 99%
“…The main compounds responsible for the most intense aromas in Sauvignon Blanc wines have been assumed to be methoxypyrazines and varietal thiols in the Marlborough region [12].…”
Section: Occurrence Of Aroma Compounds Contributing To Wine Flavormentioning
confidence: 99%